PEMANFAATAN LAHAN PRODUKTIF MELALUI PROGRAM PENANAMAN VANILI DI DESA SITUHIYANG KABUPATEN SUMEDANG - Apriani, Kiki Rizki Apriani; Junior, R. Sonny Soerojo; Diani, Irna; Ruslan; Wahyudin, Denih; Sukmana, Arief Wibawa (LPPM UKRI, 2026)
The community service program in Situheyang Village, Sumedang Regency, was initiated due to suboptimal land utilization and limited community knowledge of high-value crops such as vanilla. This program aims to improve local skills in vanilla cultivation and encourage productive land use to increase community income. The methods used include socialization and hands-on training. The results show improved understanding and skills, indicated by successful vanilla seedling planting on residents’ farmland and growing interest in developing vanilla as a leading commodity. Additionally, community groups focused on sustainable cultivation have emerged, although further assistance is still needed for more optimal outcomes. Keywords: Vanilla, Land, Village, Situhiyang